The Responses of the Quantitative Characteristics of a Ramet Population of the Ephemeroid Rhizomatous Sedge Carex physodes to the Moisture Content of the Soil in Various Locations on Sand Dunes - Buhailiqiemu Abudureheman; Huiliang Liu; Daoyuan Zhang; Kaiyun Guan; Yongkuan Zhang (The Scientific World Journal)
In this study, the soil moisture content was measured, and the quantitative characteristics of this sedge species were compared. The phenotypic plasticity of each parameter and the linear regression relationships were analyzed. The results showed that the soil moisture content was significantly affected by location, soil depth, and sampling date. The aboveground biomass, underground biomass, biomass density, and population density at the peak were significantly higher than elsewhere on the dune. However, the morphological plasticity index of the quantitative characteristics was higher at the base and middle of the dune. When the soil moisture content decreased, the underground biomass and ramet biomass density increased. The aboveground and underground biomasses were strongly negatively correlated, but the ramet height and aboveground biomass were strongly positively correlated. These results indicated that the soil water content significantly affected the clonal growth of C. physodes. The responsiveness of C. physodes may be adaptive when the soil resource supply is low. The strong morphological plasticity of the species appears to be ecologically important for the maintenance and dominance of this species in the dune habitat.